Plant community composition affects the species biogeochemical niche. Issue 5 (8th May 2017) - Urbina, Ifigenia; Sardans, Jordi; Grau, Oriol; Beierkuhnlein, Carl; Jentsch, Anke; Kreyling, Jüergen; Peñuelas, Josep
Abstract: Nutrients are essential for plant development, and their availability and stoichiometric ratios can influence the composition of plant communities. We investigated the possibility of the reverse influence: whether the conditions of contrasting species coexistence determine foliar element concentrations and plant stoichiometry, that is, species biogeochemical niche (BN). The experiment was conducted at the Ecological‐Botanical Garden of the University of Bayreuth, Germany. We analyzed foliar element concentrations of two dwarf shrubs ( Calluna vulgaris and Vaccinium myrtillus ) and two grasses ( Holcus lanatus and Arrhenatherum elatius ) growing in different community compositions (monocultures and various mixed stands). Foliar nutrient concentrations and stoichiometry (taken as a proxy of species BN) were species specific; each species showed its own BN in all communities. Furthermore, V. myrtillus and H. lanatus species shifted their BN in response to changes in their community, accomplishing the " biogeochemical niche displacement " hypothesis. We conclude that plants can readjust their foliar element concentration if they grow in communities with contrasting plant composition, suggesting a differential use of element resources when the patterns of species coexistence change. These results also support the complementary niche hypothesis.